Can Latin American Voters see the Future? Citizen Forecasting in Argentina - Thompson-Collart, Brian; Brie, Evelyne; Dufresne, Yannick (Revista Latinoamericana de Opinión Pública, 2024)
The present study examined whether Argentinian citizens could predict election results at the sub-national level. We targeted Argentinian Twitter users in seven provinces with polls using Twitter Ads. Argentinian Twitter users constitute a high-ability subgroup that possesses several characteristics that enhance citizen forecasting competence. The polls asked citizens to predict what party would win the first round of the upcoming presidential election in their province. We present a preliminary citizen forecast of the first round of the 2023 Argentinian presidential election. The forecast demonstrates three preliminary findings. First, citizens expect a competitive election in their respective provinces. Second, citizens in almost all the provinces expect an opposition victory. Finally, a high degree of uncertainty surrounds these predictions, with no party obtaining a greater than 50 percent probability of winning in any of the provinces.